دور الرقابة الداخلية في تحسين جودة القوائم المالية - حمو, عبد الله (My University, 2020)
The role of internal control in calculating the quality of financial statements. This study aims to identify the role of internal control in improving the quality of financial statements, based on a set of references on the subject 'books, magazines, websites, etc.' and to achieve the objectives of this study and test its hypotheses we have designed a questionnaire which we distributed to the auditors involved and responsible for the internal control process, and one of the most important results is that the internal control system is an essential factor in achieving the organization’s objectives, used by the institution to evaluate the performance of its various activities: accounting, financial, operational and administrative, To detect its weaknesses and alert the organization of future risks and make recommendations to address it, this system also provides adequate assurances that financial statements can be relied upon as high quality.
Keywords: Internal control, financial statements, economic institutions